Power Equilibrium Among the Organs of the State: A Critical Analysis (Teacher Half-Yearly Journal, 2025)
The paper explores and explains the legal system as the central nervous system to balance the three pillars of political power of governance from Nepalese perspective. The key question is “How do the legal practices create a triangular equilibrium of political power among the organs of state for effective governance of Nepal?” This paper addresses the problem by adopting the qualitative research design, which enables the researcher to explore and explain the holistic phenomena like legal practices that binds and creates an equilibrium state between the three key political powers of governance: Legislation, Executive and Judicial powers. The case studies are both based on court practices with participant experiences as well as the secondary source artifacts for the completion of the paper. The interpretation concluded that the state powers such as legislative, executive and judicial powers need to be maintained at equilibrium through legal framework of constitution and courtroom epiphanies of judge made laws i.e. precedence.